Is methicillin-resistant Staphylococcus Aureus infection associated with higher mortality and morbidity in hospitalized patients? A cohort study of 551 patients from South Western India - Chatterjee A; Rai S; Guddattu V; Mukhopadhyay C; Saravu K (Dove Medical Press, 2018)
Aparajita Chatterjee,1 Shipra Rai,1 Vasudeva Guddattu,2 Chiranjay Mukhopadhyay,3 Kavitha Saravu1,4 1Department of Medicine, Kasturba Medical College, Manipal Academy of Higher Education (MAHE), Manipal, Madhav Nagar, Karnataka, India; 2Department of Statistics, Prasanna School of Public Health, Manipal Academy of Higher Education (MAHE), Manipal, Madhav Nagar, Karnataka, India; 3Department of Microbiology, Kasturba Medical College Manipal Academy of Higher Education (MAHE), Manipal, Madhav Nagar, Karnataka, India; 4Manipal McGill Center for Infectious Diseases, Prasanna School of Public Health, Manipal Academy of Higher Education (MAHE), Manipal, Madhav Nagar, Karnataka, India Purpose: To determine morbidity and mortality of methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-sensitive S. aureus (MSSA) infections in a tertiary health care facility.Methods: A cohort study among hospitalized adult patients with culture proven MRSA or MSSA monoinfection were recruited in a tertiary referral center in South India from November 2011 to December 2012.Results: Of total 551 subjects, 284 (52%) had MRSA and 267 (48%) MSSA infection. A total of 184 (65%) subjects had health care-associated MRSA (HA-MRSA) and 100 (35%) community-associated MRSA (CA-MRSA). Chronic kidney disease and recent antibiotic use had significant association with MRSA. MRSA patients had significant respiratory infection (OR 2.24 [1.04, 5.16]) and bacteremia (OR 2.24 [10.40, 5.16]), relative to MSSA. MSSA group had better survival function compared to MRSA group (P=0.028). Median duration of ICU stays were 5 days (IQR 4, 8) and 2 days (IQR 2, 2) in MRSA and MSSA, respectively. Complications such as acute kidney injury, sepsis, multiorgan dysfunction, need for supportive measures were more in the MRSA group.Conclusion: MRSA imposes a huge burden in Indian scenario and HA-MRSA remains the main culprit. Patients with history of chronic kidney disease and recent use of antibiotics were found to be at a higher risk. Patients with MRSA infections tend to have poorer outcomes in terms of longer hospital stay, greater complications, and mortality. Keywords: methicillin-resistant Staphylococcus aureus, Staphylococcus aureus, risk factors, outcome, mortality, India, prognosis, impact, morbidity